FPGA based flexible UWB pulse transmitter using EM subtraction. Issue 19 (1st September 2013) - Strackx, M.; Faes, B.; D'Agostino, E.; Leroux, P.; Reynaert, P.
Abstract : An all‐digital field programmable gate array based electromagnetic subtraction technique for direct UWB pulse generation is presented. Using this technique, it is possible to generate Gaussian pulses, monocycles or doublets with high flexibility using a single printed circuit board layout. User‐controlled parameters include amplitude, pulse‐width, pulse‐type, repetition rate or even modulation. Measurements indicate a Gaussian pulse with 1.24 V peak amplitude and a 10% pulse‐width of 670 ps can be transmitted at a repetition frequency of 100 MHz. The corresponding − 10 dB bandwidth is 2.8 GHz.